Synthesis And Characterization Of Some 1,3,4 - Thiadiazole Derivatives - Majeed, Ismaeel Y.; Mustafa, Iman F.; Mahmoud, Muhand J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A series of N- benzoyl  - 2 â€“ alkyl -1- ( 2- thio â€“ 1,3,4- thiadiazole -5- yl ) , have been synthesized from DL- Î±â€“ amino acids , The methyl and sulfon thio ethers of these compounds were also prepared , representative samples of the prepared compounds were characterized from their IR- spectrum and elemental analysis .